Study on Hemolytic Uremic Syndrome Complicating Invasive Streptococcus pneumoniae Infections: Tunisian Experience - Hammi Yousra; Sayari Taha; Chaffai Haifa; Borgi Aida; Jallouli Manel; Abidi Kamel; Bouziri Asma; Khaldi Ammar; Gorgi Yousr; Ben Abdallah Taieb; et al. (Highlights on Medicine and Medical Research Vol. 6, 2021)
Hemolytic uremic syndrome (HUS), characterized by the triad of micro-angiopathic hemolytic anemia, thrombocytopenia, and acute renal insufficiency, is a common cause of acute renal failure in children. It usually follows an episode of gastroenteritis with enterotoxigenic Escherichia coli and is termed typical HUS. However, HUS is also a complication of invasive pneumococcal infection. Reasons for not diagnosing this condition include the absence of a specific laboratory test, the lack of consistent case definitions, unfamiliarity, a misdiagnosis of disseminated intravascular coagulation (DIC) and cases with micro-angiopathic hemolytic anemia and only mild renal injury. The aim of our study is to describe the epidemiology, the treatment and the evolution of HUS after invasive pneumococcal infections in Tunisia. Cases were identified between 2008 and 2016. Infection with S. pneumoniae was confirmed with culture of cerebrospinal fluid, pleural fluid, or blood. Eight children fulfilled our criteria for inclusion in the study. Primary patterns were fever, respiratory signs, neurological signs and uncommon patterns. Pneumonia was a presenting feature in 6 of 8 cases (75%), two patients had confirmed pneumococcal meningitis. Pneumococcal invasive infection was confirmed by positive yield for S. pneumoniae by culture in pleural levy or drainage in two cases, cerebrospinal fluid in two cases and blood in four cases. The mean duration of hospitalization was 23.5 days. Antibiotic therapy was initiated in all patients. Six patients from eight required dialysis for a median 27.8 days. No patients received plasma exchange therapy. Two patients died and. One patient with pneumococcal pneumatocele and presented a sepsis complicated with a nosocomial infection following a prolonged stay in the intensive care unit. One patient had bronchiectasis leading to recurrent broncho-pulmonary infections. One patient who was dialysis dependent at discharge died 4 months later.